Pengembangan Sistem Pencatatan Kerusakan Infrastruktur dan Inventaris di Dinas Komunikasi dan Informatika Provinsi Jawa Barat - Anggun Pratiwi; Rian Andrian (Jurnal Ilmiah Wahana Pendidikan, 2023)
Almost all systems in Diskominfo Jawa Barat have involved technology in it. But some systems, especially in the field of recording damage and inventory (archive) are still not well organized that make all history of damage to goods or goods that have been repaired do not have recording data. Coordinator of the First Expert Computer Pranata Diskominfo Jawa Barat, one of which is responsible for managing the recording of the recording of damage to the goods, find it difficult to see what items must be repaired and what items have been repaired. Given the need for recording as an archive of every work done. Based on the problems described above, the use of information technology systems will support the problem. Therefore, the author will design a website -based information system that can recap data with a system and data storage using a computerized database. In designing this system the author applies the design thinking.